on Graceful Chromatic Number of Vertex amalgamation of Tree Graph Family - Arika Indah Kristiana; Ahmad Aji; Edy Wihardjo; Deddy Setiawan (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2022)
Proper vertex coloring c of a graph G is a graceful coloring if c is a graceful k-coloring for k∈{1,2,3,…}. Definition graceful k-coloring of a graph G=(V,E) is a proper vertex coloring c:V(G)→{1,2,…,k);k≥2, which induces a proper edge coloring c':E(G)→{1,2,…,k-1} defined c'(uv)=|c(u)-c(v)|. The minimum vertex coloring from graph G can  be colored with graceful coloring called a graceful chromatic number with notation χg (G). In this paper, we will investigate the graceful chromatic number of vertex amalgamation of tree graph family with some graph is path graph, centipede graph, broom and E graph.